A systematic review of the use and reporting of evaluation frameworks within evaluations of physical activity interventions - Judith F. Fynn; Wendy Hardeman; Karen Milton; Joseph Murphy; Andy Jones (BMC, 2020)
Abstract Background Evaluation of physical activity interventions is vital to inform, and justify, evidence-based policy and practice to support population-wide changes in physical activity. Several evaluation frameworks and guidance documents have been developed to facilitate the evaluation and reporting of evaluation studies in public health. However, there is a lack of evidence about whether frameworks are being used to guide evaluation. There continues to be claims of poor and inconsistent reporting in evaluation studies. The aim of this review was to assess the use of evaluation frameworks and the quality of reporting of how they were applied within evaluation studies of physical activity interventions. Objectives 1. To identify whether evaluation frameworks are reported to have been used within evaluation studies of physical activity interventions, and which frameworks have been used. 2. To appraise the quality of reporting with regards to how evaluation frameworks have been used. Method We developed a checklist of indicators to enable a critical appraisal of the use and reporting of different evaluation frameworks in evaluation studies. We conducted a systematic search and review of evaluation studies published between 2015 and the date of the search to appraise the use and reporting of evaluation frameworks. A narrative synthesis is provided. Results The review identified 292 evaluation studies of physical activity interventions, only 69 (23%) of these mentioned using an evaluation framework, and only 16 different frameworks were referred to. There was variation in the quality of reporting of framework use. 51 (74%) studies were identified as being explicitly based on the stated framework, however only 26 (38%) provided detailed descriptions consistently across all the checklist indicators. Details of adaptations and limitations in how frameworks were applied were less frequently reported. The review also highlighted variability in the reporting of intervention components. More consistent and precise reporting of framework and intervention components is needed. Conclusion Evaluation frameworks can facilitate a more systematic evaluation report and we argue their limited use suggests missed opportunities to apply frameworks to guide evaluation and reporting in evaluation studies. Variability in the quality of reporting of framework use limits the comparability and transferability of evidence. Where a framework has been used, the checklist of indicators can be employed to facilitate the reporting of an evaluation study and to review the quality of an evaluation report.